Effectiveness of Information and Communication Technology based Advisory Services in Addressing Information Need of Rural Women: A Case of Connecting Dream Foundation - Rabeesh K. Verma, Monika Wason2R.N. Padaria, Premlata Singh, Sujit Sarkar, Arpan Bhowmik (Indian Journal of Extension Education, 2023)
Over the period of time many information and communication technology based projects have emerged in India, supplemented traditional extension services by providing information to various stakeholders. But accessibility of information remain a challenge for most of the people particularly rural women because of poor infrastructure support, illiteracy,lack of skilled and many others. This creates a information gap between men and women and this gap was more widen for rural women. Information and communication technologies and tools have potential to provide solution to existing information asymmetry in various lagging sectors like agriculture and can ensure more equitable information share and thus helps in empowering rural women. Connecting Dream Foundation (an ngo’s)ICT based project have made significant contribution in information dissemination on diverse range of subjects and thus helps in reducing information gap for rural women by focusing on women information needs.The present study was undertaken for assessing its effectiveness in information dissemination and advisory services to rural women in two districts of Uttar Pradesh Hapur and Ghaziabad where Connecting Dream Foundation was working since last four years. Data were collected from 120 respondents (rural women) who were associated with CDF. The effectiveness was measured by effectiveness index developed for the purpose. The study revealed that the advisory services rendered by Connecting Dream foundation was found effective.